2021
DOI: 10.4111/icu.20210105
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the pretreatment serum albumin to globulin ratio for predicting adverse pathology in patients undergoing radical prostatectomy for prostate cancer

Abstract: Purpose Few studies have demonstrated the clinical significance of pretreatment serum albumin and globulin in prostate cancer (PCa). This study evaluated the association between the pretreatment albumin to globulin ratio (AGR) and clinicopathologic characteristics of nonmetastatic PCa in a large multicenter setting in Korea. Materials and Methods This study involved 742 patients with nonmetastatic PCa who underwent radical prostatectomy (RP) in seven institutions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Recently, studies have shown that AGR can be used as an economic and practical marker to evaluate the therapeutic effect and prognosis of different cancers ( 15 17 , 38 ). Similarly, for UC patients, most studies identified that AGR before treatment was an independent prognostic factor in multivariate analysis ( 22 – 29 , 31 , 32 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that AGR can be used as an economic and practical marker to evaluate the therapeutic effect and prognosis of different cancers ( 15 17 , 38 ). Similarly, for UC patients, most studies identified that AGR before treatment was an independent prognostic factor in multivariate analysis ( 22 – 29 , 31 , 32 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the four articles selected for the review [ 18 , 19 , 20 , 21 ], all studies were retrospective mono or multicenter clinical trials ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…All these studies defined the patient population in terms of clinical (age, PSA values), pathologic characteristics (staging, histologic grading) and progression (mainly biochemical (BCP)) after treatments. Two retrospective analyses [ 19 , 20 ] included non-metastatic PC cases considered for radical prostatectomy (RP), one [ 18 ] metastatic PC submitted to androgen deprivation therapies (ADT) and one [ 21 ] non-metastatic PC submitted to salvage RP after radiation therapy ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations